PENGARUH KUALITAS PRODUK, IKLAN DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN SABUN MANDI LUX CAIR (Studi kasus pada konsumen/pengguna sabun mandi lux cair di swalayan Gelael Mall Ciputra Semarang) - Luffi Sidrotul Muntaha; Handoyo Djoko Waluyo; Reni Shinta Dewi (Universitas Diponegoro, 2015)
This study aims to determine the effect of product quality, advertising and brand image on purchase decisions Lux liquid soap. The population in this study were the users of lux soap liquid in Gelalel Mall Ciputra Semarang. The research sample of 100 respondents was taken and the sampling technique used was purposive sampling technique, meaning that the sampling technique in accordance with certain criteria. Measurement scale using a Likert scale. Analysis of data using simple linear regression and multiple linear regression with SPSS 16.0. Based on the survey results revealed that the quality of products, advertising and brand image and signifikanterhadap positive influence purchasing decisions, either partially or simultaneously. Variable product quality influence on purchase decisions is equal to 24.1%. Advertising variable influence on purchase decisions is equal to 15.6%. Variables brand image influence on purchase decisions in the amount of 53%. Simultaneously, the variable quality of the product, advertising and brand image influence the purchase decisions of 55.5%. This means that the better the quality of the product, advertising in accordance with the wishes of customers, as well as the high value of the brand image, it can improve the buying decision.